2007
DOI: 10.1021/bi061318s
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Microtubule Binding Properties of Tau Mutants of Frontotemporal Dementias

Abstract: Several mutations in the gene encoding the microtubule-associated protein tau are responsible for the formation of neurofibrillary inclusions in frontotemporal dementia with Parkinsonism linked to chromosome 17 (FTDP-17). Here we present the high-resolution characterization of the conformational properties of two FTDP-17 mutants of the four-repeat domain of tau, P301L and DeltaK280, and their properties for binding to polyanions and microtubules. Multidimensional NMR spectroscopy shows that the mutations do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
89
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 55 publications
13
89
0
Order By: Relevance
“…To test if the binding sites identified by the NMR titrations of K32 with MT are characteristic also for the strong primary binding of Tau to MTs, we repeated the K32-MT titration at increased ionic strengths. Previous studies have shown that in the presence of sodium chloride, the MT-binding strength of Tau is reduced and the weaker, nonsaturable binding is strongly attenuated (34). In agreement with these results, the addition of 100 mM NaCl to the Tau-MT solution (K32: MT ϭ 2:1) increased the average ratio of signal intensities to about 80% (data not shown).…”
Section: Backbone Assignment Of K32-nmr Resonances Insupporting
confidence: 86%
“…To test if the binding sites identified by the NMR titrations of K32 with MT are characteristic also for the strong primary binding of Tau to MTs, we repeated the K32-MT titration at increased ionic strengths. Previous studies have shown that in the presence of sodium chloride, the MT-binding strength of Tau is reduced and the weaker, nonsaturable binding is strongly attenuated (34). In agreement with these results, the addition of 100 mM NaCl to the Tau-MT solution (K32: MT ϭ 2:1) increased the average ratio of signal intensities to about 80% (data not shown).…”
Section: Backbone Assignment Of K32-nmr Resonances Insupporting
confidence: 86%
“…Hyperphosphorylation or pro‐aggregation mutations, which increase the β‐sheet propensity in the repeat domain of tau and lead to tau oligomerization and aggregation (Fischer et al , 2007), lead to changes in the protein charge and conformation; these changes appear to be crucial for the phase separation into droplets. For example, the N‐terminal half of tau (tau256), which is a priori zwitterionic and disordered, gains LLPS capacity when negative charges are introduced by phosphorylation in the otherwise positively charged proline‐rich regions (P1 + P2), thereby neutralizing or inverting the local charge excess.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in MT stability, abnormal tau accumulation is linked to the pathology of a number of neurodegenerative diseases including Alzheimer's disease (AD), frontotemporal dementia (FTD), Pick's disease and chronic traumatic encephalopathy (26). Several of these tauopathies are characterized by mutations in the MAPT gene resulting in tau protein mutations that can compromise tau-mediated MT stabilization (27,28).…”
Section: Introductionmentioning
confidence: 99%